Giant haemangioma of the naso-orohypopharynx treated by midline mandible split - Ramalingam, KK; Ramalingam, Ravi; Rayappa, C; Chaudhary, Ashlesha B (Bangladesh Journal of Otorhinolaryngology, 2011)
Hemangioma is a benign tumour characterised by an increased number of normal or abnormal blood vessels. A 22-year-old male presented with occassional hemoptysis of 3 weeks duration. Clinical examination revealed an angry looking red mass in the oropharynx suggestive of hemangioma. MRI and MRAngiography revealed the mass to be a hemangioma extending from the skull base to the vocal cord level. The hemangioma was excised surgically using a midline labio mandibulo glossotomy approach. Follow up till date has been uneventful. Key words: Haemangioma; Phayrnx DOI: 10.3329/bjo.v17i1.7631 Bangladesh J Otorhinolaryngol 2011; 17(1): 62-67